A theoretical approach on membrane characterization: the deduction of fine structural details of asymmetric nanofiltration membranes - Hassan, A. R.; Ali, Nora'aini; Abdull, Norhidayah; Ismail, A. F. (Elsevier Science B.V., Amsterdam, 2007)
In this study, the effects of polymer concentration on the performances and fine structural details of asymmetric nanofiltration (NF) membranes were investigated. Based on the well known models/equations on pore flow, solution diffusion and extended Nernst–Planck, the experimental data (electrolyte/ions rejection) has been modeled. Spielger– Kedem equations were used to determine the membranes parameters such as reflection coefficient, solute permeability and steric hindrance effects. Employing steric hindrance pore model (SHP) model and Teorell–Meyer Sievers (TMS) model, important membranes structural details in terms of effective pore radius, effective charge density and ratio of effective membrane thickness to membrane porosity have been measured. From the modeling results, it was found that the polymer concentration can influence the membrane performances by varying of structural details. Through the observation using scanning electron microscopy (SEM), it was shown that the produced membranes exhibited a finger-like structure. According to the results obtained from the modeling, these membranes are in range of the commercially available NF membranes.